Pengaruh Literasi Digital dan Literasi Keuangan Terhadap Kinerja UMKM Dengan Penggunaan Sistem Informasi Akuntansi Sebagai Variabel Mediasi - Amelia, Syafrila Putri Nur; Diana, Nur; Nandiroh, Umi (Universitas Islam Malang, 2026)
This study aims to examine and analyze the effect of digital literacy and financial literacy on the performance of micro, small, and medium enterprises (MSMEs), with accounting information systems as a mediating variable. The study employs a quantitative approach using a survey method. Primary data were collected through questionnaires distributed to 100 MSME owners/managers domiciled in Blimbing District and Lowokwaru District, Malang City. The data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results indicate that improvements in MSME performance are influenced by the digital literacy and financial literacy of MSME actors. However, the use of accounting information systems as a mediating variable does not show a significant effect, due to the limited understanding among MSME actors regarding the role of accounting information systems in overcoming decision-making barriers. This lack of understanding hinders their ability to utilize accounting information systems to comprehend financial conditions, plan business strategies, control costs, and enhance accountability.Keywords: Digital literacy, financial literacy, accounting information system, msmes.